Awareness of quantity of ORS and Zinc among mothers of under five children with diarrhoea at a tertiary care Centre Lahore - Mubeen Nazar Duggal; Attia Bari; Ayesha Mansoor; Sara Saeed; Wajiha Rizwan; Javeria Nayar (Journal of the Pakistan Medical Association, 2021)
Abstract Objectives: To assess mothers’ knowledge about quantity of ORS and zinc in management of diarrhoea. Methods: Cross sectional study conducted over a period of 4 months from May 2019 to August 2019 among mothers accompanying under five children admitted in the diarrhoea ward of The Children’s hospital Lahore for rehydration and included 334 children age 2 months to 59 months. Data was collected regarding age, sex, residence, number of children in house hold, socioeconomic status, maternal literacy status, mother’s awareness of signs of dehydration in diarrhoea, familiarity with the term oral rehydration salt (ORS) as regards its correct preparation and administration and Zinc supplementation in diarrhoea. Conclusion: Majority mothers were aware of ORS and doctors were the main source of information. Many knew the correct role of ORS in diarrhoea and its method of preparation as sachet pack was the most commonly used type. Although ORS use rate was high, but most mothers were unaware of quantity of ORS to be given. Zinc use in diarrhoea was very low in our study. Keywords: Awareness, ORS, Zinc, Diarrhoea.